Direct deoxygenation of α-hydroxy and α,β-dihydroxy ketones using a silyl lithium reagent - Zade, Vishal M.; Gangnale, Laxmikant D.; Athawale, Paresh R.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2023)
A reliable method for the one-step direct deoxygenation of alpha-hydroxy ketones has been developed using a silyl lithium reagent and acetic anhydride. The method is metal-catalyst-free and does not require prefunctionalization of the hydroxy group prior to its removal. Deoxygenation of different primary, secondary, and tertiary alcohols was carried out with up to 98% isolated yield. Additionally, double deoxygenation was achieved when the present method was applied to alpha,beta-dihydroxy ketones to access the corresponding enones in a single step.